Механізм формування системи стратегічного управління розвитком промислового підприємства - Харченко, В.А. (Економіка промисловості, 2014)
Розкрито механізм формування системи стратегічного управління розвитком: досліджено його компоненти (мета, завдання, засоби, методи і керовані елементи), обґрунтовано ціль і завдання за базовими і підтримуючими механізмами, встановлено основні взаємозв’язки між базовими механізмами формування системи, завданнями і функціями побудови системи. Раскрыт механизм формирования системы стратегического управления развитием: исследованы его компоненты (цель, задачи, средства, методы и управляемые элементы), обоснованы цель и задачи базовых и поддерживающих механизмов, установлены основные взаимосвязи между базовыми механизмами формирования системы, задачами и функциями построения системы. The article aims at examining the mechanism of formation of the strategic management system of industrial enterprise development. In this connection the contents of the development management control are analyzed (the interconnections between management subsystems are described, the place of the management system in the management process is defined), the components of the system formation are examined (aim, tasks, means, methods and managed elements). The aim and tasks of basic and supporting mechanisms of the system formation are grounded. The main interconnections between the basic mechanisms of the system formation, tasks and functions of the system formation are determined.The system of the strategic management of industrial enterprise development as a set of subsystems of external and internal state is analyzed. The subsystem of the internal state is presented in the form of a cube. Vertical faces are internal subsystems: the subsystems of production, product realization, financial state, resource state. The subsystem of the external state is presented in the form of a pentagon. Five faces of the figure stand for the factors that influence enterprises’ activity. They are economic, political, market, and social factors, which must be taken into consideration in the process of making managerial decisions.There are defined three basic mechanisms of the development management system formation: the mechanism of systemic management decision-making, the mechanism of conformity of management aims by managed elements of each subsystem, the mechanism of ensuring interaction of management subsystems. The first mechanism is connected with the realization of the control function, the second one with the aim determination and the last one with the coordination function.The basis of the supporting mechanisms is made of development, management processes and the notion of a system. This is the mechanism of development management, the mechanism of dynamic integration of management levels, and the mechanism of systemic activity direction.